2020
DOI: 10.1007/s11090-020-10079-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted ALD of Highly Conductive HfNx: On the Effect of Energetic Ions on Film Microstructure

Abstract: In this work, we report on the atomic layer deposition (ALD) of HfN x thin films by employing CpHf(NMe 2) 3 as the Hf(IV) precursor and Ar-H 2 plasma in combination with external RF substrate biasing as the co-reactant. Following up on our previous results based on an H 2 plasma and external RF substrate biasing, here we address the effect of ions with a larger mass and higher energy impinging on HfN x film surface during growth. We show that an increase in the average ion energy up to 304 eV leads to a very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
(121 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, Karwal et al. [ 14 ] have shown that the impact of high‐energy ions during the PEALD film growth could significantly improve the chemical and electrical properties of the afforded HfN x films. Second, as a noble gas, argon can stabilize the plasma discharge, making the energy density of the plasma more uniform, and ultimately improving the uniformity of the films.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Karwal et al. [ 14 ] have shown that the impact of high‐energy ions during the PEALD film growth could significantly improve the chemical and electrical properties of the afforded HfN x films. Second, as a noble gas, argon can stabilize the plasma discharge, making the energy density of the plasma more uniform, and ultimately improving the uniformity of the films.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ion energy control during plasma-enhanced atomic layer deposition (ALD) with RF sinusoidal waveform biasing has been demonstrated to enable control over the growth and material properties of thin films. 53,[55][56][57][58] Using the FIG. 6.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrides such as ZrN and HfN have similarly strong covalent bonds [59] but their refractory nature makes them especially difficult to synthesize and process. The stoichiometric nitrogen content can be varied in these complexes and relates to their synthetic techniques [63][64][65]. Boride UHTCs, such as HfB 2 and ZrB 2 , benefit from very strong bonding between boron atoms as well as strong metal to boron bonds; the hexagonal close-packed structure with alternating two-dimensional (2D) boron and metal sheets gives these materials high and anisotropic strength as single crystals (Fig.…”
Section: Lattice Structure Of Uhtcsmentioning
confidence: 99%